BUSINESS EXCELLENCEINITIATIVES: A STUDY OF DUBAI QUALITY AWARD-WINNING ORGANIZATIONSIN UAE - Mehran Doulatabadi; Hajime Ushimaru; Azizah Yusof (Bina Nusantara University, 2020)
This paperpresentsthe central results of a survey analysis carried out in the UAE with respect to business excellence initiatives. The main purpose of this research is to investigate the use of business excellenceinitiativesin Dubai quality award-wining organizations. Thestudyused a self-administered questionnairetoconfirm the adaptability of business excellence initiativesby Dubai quality award-wining organizations. Several statistical tests including descriptive statistics, internal consistency reliability and content validitywere employed using the Statistical Package for the Social Sciences(SPSS). The result of the study shows that various business excellence initiatives already implemented byDubai quality award-wining organizations for their efforts towards business excellence. The award-wining organizations believe that business excellenceinitiatives areimportant in helping them reach their organizational goals.